Scenario and Incentives of Foreign Direct Investment (FDI) in Bangladesh (Global Journal of Management and Business Research, 2013)
FDI is considered as an important tool for economic development of developing country. The term foreign direct investment is considered as one of the important contributors for the economic development of a country in particular and the world in general with the concept of globalization. Foreign direct investment has great impact on the development of developing country like Bangladesh. Foreign Direct Investment increases trade and investment, labor mobility, capital inflow, technology and know-how to the recipient country.
Keywords: Development; Foreign Direct Investment (FDI); Incentives